2023
DOI: 10.1038/s41598-023-28409-2
|View full text |Cite
|
Sign up to set email alerts
|

Schooling behavior driven complexities in a fear-induced prey–predator system with harvesting under deterministic and stochastic environments

Abstract: The well-being of humans is closely linked to the well-being of species in any ecosystem, but the relationship between humans and nature has changed over time as societies have become more industrialized. In order to ensure the future of our ecosystems, we need to protect our planet’s biodiversity. In this work, a prey–predator model with fear dropping prey’s birth as well as death rates and nonlinear harvesting, is investigated. In addition, we consider that the consumption rate of predators, i.e., the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The perturbations in noise intensity have the potential to disrupt the stability of deterministic equilibrium points, introducing a form of instability, often termed weak stability, in natural systems. In stochasticity, this phenomenon is recognized as the emergence of stationary distributions [17]. To explore the impact of environmental white noise on the dynamics of the predator-prey system under consideration, we visualize the solution trajectories of both the stochastic system and its corresponding deterministic counterpart.…”
Section: Numerical Observations Of the Stochastic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The perturbations in noise intensity have the potential to disrupt the stability of deterministic equilibrium points, introducing a form of instability, often termed weak stability, in natural systems. In stochasticity, this phenomenon is recognized as the emergence of stationary distributions [17]. To explore the impact of environmental white noise on the dynamics of the predator-prey system under consideration, we visualize the solution trajectories of both the stochastic system and its corresponding deterministic counterpart.…”
Section: Numerical Observations Of the Stochastic Systemmentioning
confidence: 99%
“…However, higher noise intensity can drive populations to extinction [6]. Investigations on fear‐induced prey–predator systems with stochastic environments revealed that under lower environmental disturbances, model species fluctuate around average deterministic steady‐state values, while higher disturbances lead to species extinction [17]. Research assessing the impact of environmental noise on prey–predator interactions with seasonal water level fluctuations highlighted the significant roles played by noise intensity and water level variations in aquatic systems [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation